Recita, em nome do teu senhor: as raízes judaico-cristãs do movimento proto-islâmico e os profetismos na Península Arábica (séc. VII E.C.) - Paulo Renato Silva de Andrade (2017)
This text's main purpose is to contribute to the understanding of the emergence of Muhammad's prophetic movement on 7th century Arabia through its relation with the JudeoChristian communities and cultures at the peninsula. Starting from a sociological and anthropological overview of its inhabitants, as well as their political structures, the text endeavors an inquiry on the evidences of the presence of Jewish and Christian communities in the region, and outlines some of their characteristics, both political and cultural. To do so, it makes use of a diverse documental corpus, including narrative, epigraphic and archeological evidence, with different origins and from different timespans. From this ethnographic survey, it proceeds to an analysis of the many Arabian prophetic political movements, contemporaneous with Muhammad's, and their main characters to whom the Islamic tradition would grant the status of false-prophets. It is our understanding that the careful cross-analysis of these relatively understudied phenomena contributes to shed some light on the political-cultural milieu in which the prophet of Islam would preach his message, and ultimately, to a better understanding of the foundations and limits of Early-Islam.